Case study: an assessment of integrated geotechnical considerations during the Hazelwood mine lake filling for mine closure using a reliability-based approach - Narendranathan, S; Butler, J; Kuang, K; Lowe, J; Moran, A (Mine Closure 2024: 17th International Conference on Mine Closure, 2024)
The Hazelwood mine (Latrobe Valley, Victoria, Australia) is currently in the process of being rehabilitated following mine closure. The planned final landform concept incorporates a full pit lake. As the mine transitions from the ‘empty’ void scenario to the full pit lake, a number of geotechnical considerations need to be taken into account. These considerations include the assessment of mechanisms such as coal block sliding along critical interseams (basal geological units), kinematic (structural) considerations, ground movement (rebound) and weight balance, against floor heave. This paper presents the reliability-based assessment approach the authors undertook to understand the critical considerations during the planned lake-filling phase of the Hazelwood mine for closure, and the manner in which these were assessed using reliability-based metrics.
Keywords: Latrobe Valley; brown coal; mine; geotechnical; batter; stability; reliability; index; floor heave